Analysis of puff dynamics in oocytes: Interdependence of puff amplitude and interpuff interval - Fraiman, D. (2006)
Puffs are localized Ca2+ signals that arise in oocytes in response to inositol 1,4,5-trisphosphate (IP3). They are analogous to the sparks of myocytes and are believed to be the result of the liberation of Ca2+ from the endoplasmic reticulum through the coordinated opening of IP3 receptor/channels clustered at a functional release site. In this article, we analyze sequences of puffs that occur at the same site to help elucidate the mechanisms underlying puff dynamics. In particular, we show a dependence of the interpuff time on the amplitude of the preceding puff, and of the amplitude of the following puff on the preceding interval. These relationships can be accounted for by an inhibitory role of the Ca2+ that is liberated during puffs. We construct a stochastic model for a cluster of IP3 receptor/channels that quantitatively replicates the observed behavior, and we determine that the characteristic time for a channel to escape from the inhibitory state is of the order of seconds. © 2006 by the Biophysical Society.